2016
DOI: 10.3390/f7040081
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Relationships of Melia Taxa in China Assayed with Sequence-Related Amplified Polymorphism (SRAP) Markers

Abstract: Abstract:The uncertainty about whether, in China, the genus Melia (Meliaceae) consists of one species (M. azedarach Linnaeus) or two species (M. azedarach and M. toosendan Siebold & Zuccarini) remains to be clarified. Although the two putative species are morphologically distinguishable, genetic evidence supporting their taxonomic separation is lacking. Here, we investigated the genetic diversity and population structure of 31 Melia populations across the natural distribution range of the genus in China. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…But one cannot derive such relationships conclusively from the current study with limited data from world populations. An earlier study based on SRAP markers also reported the existence of significant intra-specific genetic polymorphism in the M. azedarach populations from China (Liao et al 2016). These observations indicated genetic complexity within M. azedarach, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But one cannot derive such relationships conclusively from the current study with limited data from world populations. An earlier study based on SRAP markers also reported the existence of significant intra-specific genetic polymorphism in the M. azedarach populations from China (Liao et al 2016). These observations indicated genetic complexity within M. azedarach, which requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Species complexity exists in Melia due to the occurrence of cultivated varieties, and morphotypes, and therefore, the number of species in this genus remains to be conclusively determined. Inter-species differentiation between the Melia species in China is ambiguous, and it is not clear whether M. toosendan Siebold exists as a separate species (Liao et al 2016). Gamble (1922) (Hajra et al 1997), M. birmanica and M. composita were synonymized under M. dubia, and M. azedarach and M. dubia were recognized as two distinct species.…”
Section: Despite Its Multipurpose Values and Importance Species Levementioning
confidence: 99%
“…Interestingly, SRAP analysis partially clustered the four BPH populations into two PCoA plots that corresponded with the two virulence groups. Therefore, apart from its analogy to the morphological character (Robarts and Wolfe 2014), SRAP markers also can elucidate markers with inherent biological significance, including phenotypes (Liao et al 2016).…”
Section: Genetic Relationshipmentioning
confidence: 99%
“…(2009) have emerged as the markers of choice due to less expensive, small amount of sample DNA requirement, clear and un-ambiguous banding pattern and higher reproducibility (Jingade et al, 2019;Shangguo et al, 2018). The SRAP markers have been effectively used in the genetic diversity and population structure analysis in number of plants such as Brassica juncea (Singh et al, 2013), Toona ciliata (Li et al, 2015), Melia taxa (Liao et al, 2016) and Coffea arabica (Jingade et al, 2019;Mishra et al, 2014). SCoT marker system targets the short conserved region of the plant genes surrounding the ATG initiation codon.…”
Section: Introductionmentioning
confidence: 99%